2008
DOI: 10.1021/ol702961v
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Aigialomycin D:  Surprising Chemoselectivity Dependence on Alkyne Structure in Nickel-Catalyzed Cyclizations

Abstract: The total synthesis of aigialomycin D was carried out using a nickel-catalyzed ynal macrocyclization as a key step. This key step allowed macrocycle assembly and formation of a disubstituted alkene and a secondary hydroxyl stereocenter in a single step, although the stereocenter was formed unselectively. An interesting side reaction involving five-membered-ring synthesis by an aldehyde/styrene cyclization was observed when macrocyclization of an alkynyl silane was attempted. A mechanistic basis for this surpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…4a,9 This limitation was confirmed in a recent attempt to access exo-selective reductive macrocyclizations 10 using existing protocols including those originating from our laboratory. 11 However, a recent disclosure from our laboratory described studies with an expanded set of ligands, wherein a broad range of alkynes participated in intermolecular reductive couplings to provide either regioisomer in a ligand-controlled process.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…4a,9 This limitation was confirmed in a recent attempt to access exo-selective reductive macrocyclizations 10 using existing protocols including those originating from our laboratory. 11 However, a recent disclosure from our laboratory described studies with an expanded set of ligands, wherein a broad range of alkynes participated in intermolecular reductive couplings to provide either regioisomer in a ligand-controlled process.…”
Section: Resultsmentioning
confidence: 65%
“…4a,9 Utilizing triethylsilane as a reducing agent and 30 mol% Ni(COD) 2 , 30 mol % IMes-HCl, and 40 mol % KO- t -Bu in THF allowed clean production of reductive endocyclization product 14 and its C7 epimer in 58% yield (Scheme 2). Notably a 4:1 dr, favoring diastereomer 14 , was obtained under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined the reaction more extensively, and in analogy to an observation made in our recent synthesis of aigialomycin D,xiii we ultimately found that employing 2.0 equiv of Garner aldehyde 1 in couplings of 2d with trace water in THF allowed reasonably efficient couplings,xiv providing the desired vinyl silane 3d in 65 % isolated yield with complete stereocontrol (>98:2 dr, >98:2 Z : E , Scheme 4). n -Bu 4 NF-mediated deprotection of 3d to 11 proceeded in 91 % isolated yield, which was followed by the 2N HCl deprotection described above (73 % yield) to complete a more direct synthesis of D- erythro -sphingosine.…”
Section: Resultsmentioning
confidence: 93%
“…The NHC catalyst is more reactive than analogous phosphinebased catalysts and a broad range of alkynes and aldehydes undergo reductive coupling under these conditions. Macrocyclization via nickel -catalyzed reductive coupling has been shown to be a powerful tool in the synthesis of several natural products, including amphidinolide T1 [41] , amphidinolide T4 [41] , ( − ) -terpestacin [42] , and aigialomycin D [43] . A general protocol for nickel -catalyzed macrocyclizations was published using ligand -based control of regioselectivity (Scheme 8.22 ) [44] .…”
Section: Simple Aldehyde and Alkyne Reductive Couplingsmentioning
confidence: 99%
“…Resorcinylic macrolides are a family of natural products that possess a 14 -membered macrolide core with a fused benzenoid subunit. A member of this family that has drawn signifi cant scientifi c attention due to its antimalarial and cytotoxic activity is aigialomycin D. In one total synthesis of aigialomycin D, late -stage nickel -catalyzed macrocyclization was employed to afford the macrocyclic core [43] . Macrolide precursor 45 was cyclized in 61% yield in a 1 : 1 diastereoselectivity.…”
Section: Use In Natural Product Synthesismentioning
confidence: 99%